Identity Crisis in Ruby Gillman, Teenage Kraken (2023): A Study of Marcia's Identity Statuses (PANOPTICON: Journal of English Studies, 2026)
This study explores the identity crisis experienced by the main character in the animated film Ruby Gillman, Teenage Kraken (2023). The object of this study is the film itself, which follows Ruby, a shy and insecure teenager who discovers that she is the descendant of a powerful sea kraken. As she struggles to fit in at high school, Ruby is forced to conceal her true nature. Her life changes dramatically when she learns of her royal lineage and inherits the kraken throne. This research aims to examine the process of identity crisis that Ruby undergoes and how she ultimately resolves it. The story depicts Ruby grappling with her identity due to both external and internal pressures, ultimately achieving a stable sense of self through exploration and self-acceptance. A qualitative method was employed, analyzing dialogue and visual scenes from the film. The theoretical framework is based on Marcia's (1966) theory of identity statuses, which comprises four categories: identity diffusion, foreclosure, moratorium, and identity achievement. The findings reveal that Ruby's identity crisis is triggered by social pressure and familial expectations, and is resolved through a process of self-exploration and acceptance of her dual identity as both human and kraken..